Date Fruit Extract (Phoenix dactylifera, Ajwa) Modulates NK Cells and TNF- Alpha in DMBA-Induced Mammary Cancer Sprague-Dawley Rats - Rehab Mohammed Mustofa Elhemeidy; Diana Lyrawati; Edi Widjajanto (Journal of Tropical Life Science, 2018)
Cellular immune system is one of anti-tumor target development. NK cells, one of major components of antitumor innate immune responses, are frequently decreased functionally during breast cancer progression, whereas TNF-alpha changes from anti-tumor into pro-tumorigenesis and its level increases with advancing cancer. In this study, we investigated the immunomodulatory effects of Ajwa date fruit extract to determine whether it stops the progression of breast cancer. Using rats induced with single dose 20 mg DMBA subcutaneously, we examined whether administration of Ajwa date fruit (Phoenix dactylifera) extract (at 400, 800 mg/kg body weight/d) post-DMBA induction for 30 days modulate NK cells, TNF-alpha, and development of breast cancer. ELISA, FACS, immunohistochemistry, and histologic observation were employed. Compared to positive control group (DMBA-induced only), we showed that the Ajwa date fruit extract normalize the level of circulatory CD161 NK cells and breast tissue TNF-alpha, cell size and proliferation, and improve overall survival rates. Ajwa date fruit extract may be used to modulate NK cells and TNF-alpha against progression of breast cancer. Further studies are required to develop date fruit extract as anti-cancer in human, whether as single or adjunct therapy to standard management of breast-cancer.